Brainwash : the secret history of mind control - Streatfeild, Dominic (London : Hodder & Stoughton, 2007)
Summary. What would it take to turn you into a suicide bomber? How would you interrogate a member of Al Qaeda? With access to formerly classified documentation and interviews from the CIA, the U.S. Army, MI5, MI6, and the British Intelligence Corps, acclaimed journalist Dominic Streatfeild traces the history of the worldʾs most secret psychological procedure. From the cold war to the height of todayʾs war on terror, groups as dissimilar as armies, religious cults, and advertising agencies have been accused of brainwashing. But what does this mean? Is it possible to erase memories or to implant them artificially? Do heavy-metal records contain subliminal messages? Do religious cults brainwash recruits? What were the CIA and MI6 doing with LSD in the 1950s? How far have the worldʾs militaries really gone? From the author of the definitive history of cocaine, Brainwash is required reading in an era of cutting-edge and often controversial interrogation practices. More than just an examination of the techniques used by the CIA, the KGB, and the Taliban, it is also a gripping, full history of the heated efforts to master the elusive, secret techniques of mind control.
Includes information on amnesia, ARTICHOKE project, Central Intelligence Agency (CIA), hypnosis, hallucinogens, interrogation, LSD, MKULTRA project, satanic ritual abuse, sensory deprivation, sleep, suicide, truth drugs, Unification Church, etc.
Keywords: 1900-luku; 2000-2009; Brainwashing -- History; Brainwashing; Psychological warfare -- Case studies; historia; psykologinen sodankäynti; tapaustutkimus; aivopesu